Harmonization of Indonesian Aviation Regulations and the Challenges of Implementing Open Sky Policy in ASEAN Single Aviation Market - Anugrah, Dikha; Neni Ruhaeni; Neni Sri Imaniyati; Eman Suparman (Universitas Kuningan, 2025)
Regional integration through ASEAN (Association of Southeast Asian Nations) Single Aviation Market (ASAM) is characterized by a complex landscape of opportunities and challenges for Indonesia, particularly considering its status as a vast archipelagic nation with intricate and evolving aviation needs. Therefore, this study aims to comprehensively analyze Indonesian position in ASAM, as well as identify any legal and institutional barriers to the implementation of the Open Sky Policy with a focus on regulatory harmonization in ASEAN aviation sector. It also aims to examine the extent to which domestic policies, specifically those protecting national airlines, interact with regional liberalization efforts. In order to achieve the stated objectives, a normative juridical approach was adopted, incorporating a conceptual and regulatory approach. The obtained results showed that the geographical characteristics of Indonesia, infrastructural disparities, and the tendency toward regulatory protectionism were the primary factors contributing to the caution in liberalizing the aviation market. Despite formal commitment to ASAM agreement, implementation in the field remains uneven due to sectoral interests and limited institutional capacity. Preventive and corrective efforts have been made through gradual policy reforms and bilateral agreements. However, the absence of a binding supranational authority was observed to significantly weaken the enforcement mechanism. Based on the observations made during the course of this exploration, an inference was made that Indonesia plays an essential but cautious role in ASAM, requiring strategic policy synchronization, infrastructure strengthening, and gradual market opening to gain benefits from regional aviation liberalization without sacrificing national interests.